2015
DOI: 10.3389/fpsyg.2015.00772
|View full text |Cite
|
Sign up to set email alerts
|

A face detection bias for horizontal orientations develops in middle childhood

Abstract: Faces are complex stimuli that can be described via intuitive facial features like the eyes, nose, and mouth, “configural” features like the distances between facial landmarks, and features that correspond to computations performed in the early visual system (e.g., oriented edges). With regard to this latter category of descriptors, adult face recognition relies disproportionately on information in specific spatial frequency and orientation bands: many recognition tasks are performed more accurately when adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
2
11
0
1
Order By: Relevance
“…In another developmental study using a face‐matching task and an extended age range (6 to 74 years of age), Goffaux, Poncin, and Schiltz () also presented evidence of a developing information bias favoring horizontal orientation energy in face images. Specifically, this study demonstrated that the tuning of the face inversion effect (Yin, ) to horizontal orientation information changes during childhood along similar lines as the time course reported by Balas, Schmidt et al (). These converging results thus suggest that high‐level mechanisms supporting face recognition continue to be tuned to low‐level orientation channels during childhood.…”
Section: Introductionsupporting
confidence: 85%
“…In another developmental study using a face‐matching task and an extended age range (6 to 74 years of age), Goffaux, Poncin, and Schiltz () also presented evidence of a developing information bias favoring horizontal orientation energy in face images. Specifically, this study demonstrated that the tuning of the face inversion effect (Yin, ) to horizontal orientation information changes during childhood along similar lines as the time course reported by Balas, Schmidt et al (). These converging results thus suggest that high‐level mechanisms supporting face recognition continue to be tuned to low‐level orientation channels during childhood.…”
Section: Introductionsupporting
confidence: 85%
“…Face specific processing was inferred based on the FIE which was significant with faces that contained horizontal information for the age groups 12–13, 14–15, 16–17, 18–19, 20–35, and >59 years of age. At the ages of 6–7, 8–9, and 10–11 years no FIE for horizontal information was observed which in line with the results presented by Balas et al (2015) suggesting progressive maturation of horizontal processing until young adulthood. At elderly adulthood, however, FIE development with faces that contained only horizontal information dropped notably with a non-linear function best fitting the FIE as a function of age.…”
Section: Discussionsupporting
confidence: 89%
“…Two recent publications add to understanding the role of horizontal information in face recognition. Balas et al (2015) tested 5–10 year olds with faces or objects (houses) that were either presented upright or inverted. Stimuli either contained vertical, horizontal or both vertical and horizontal information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the size of the face inversion effect increased from 6 years of age onwards but only for upright horizontal facial cues. On the other hand, Balas, Schmidt, and Saville () showed that the basic‐level categorization of faces (against houses) is already better at horizontal than vertical angles at 5 years of age and that this horizontal bias further develops at least until 10 years of age. In sum, these developmental results indicate that: (1) the specialization of the face processing system from childhood to young adulthood roots into the refined encoding of horizontal ranges of upright face information and that (2) the coarse categorization of a face as a face attunes to horizontal orientation earlier than the fine discrimination of individual identities.…”
Section: Introductionmentioning
confidence: 99%